Comparing the Effect of Food Security on Life Expectancy in Kalimantan and Sulawesi - Kurniawan Kurniawan; Made Kembar Sri Budhi; I Nyoman Mahaendra Yasa; Ni Made Tisnawati; Henrianto Henrianto; Desi Ade Trya (Faculty of Economics and Bussiness, Universitas Diponegoro, Semarang, Indonesia, 2025)
The second Sustainable Development Goal is to end hunger, achieve food security, improve nutrition, and promote sustainable agriculture. Food security is a key indicator for these goals. Maintaining food security is crucial to ensuring that no one goes hungry, allowing people to live healthy and long lives. This study offers new evidence explaining the influence of undernourishment, food insecurity, and stunting, with additional explanatory variables such as GDP per capita growth, education, access to adequate housing, and smoking, on life expectancy in Kalimantan and Sulawesi. This study uses panel data regression analysis techniques. It utilizes provincial-level secondary data from the Indonesian Central Bureau of Statistics for 2017-2023. Convincing evidence indicates that undernourishment has a negative and significant impact on life expectancy in Kalimantan (0.06), whereas it has no significant effect in Sulawesi. Education was the dominant variable with a positive and significant effect on life expectancy in Kalimantan (1.86) and Sulawesi (1.60). The variables of food insecurity, stunting, GDP per capita growth, access to adequate housing, and smoking did not significantly affect life expectancy in Kalimantan or Sulawesi. The path to increasing life expectancy is through education and food security maintenance. This research contributes to the literature by providing a comparative analysis of the food security-life expectancy nexus in the distinct Indonesian regions of Kalimantan and Sulawesi, offering original evidence for region-specific policy-making.